Speculation and the Rate of Interest - Black, J.; de Jasay, A. E. (Review of Economic Studies, 1957)
J. Black, A. E. de Jasay; Speculation and the Rate of Interest*, The Review of Economic Studies, Volume 24, Issue 2, 1 February 1957, Pages 95–110, https:/